Zapach idei. Synestezja i ideastezja w Correspondances Charles’a Baudelaire’a - Kozłowska, Zuzanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article constitutes a re-reading of Charles Baudelaire’s Correspondences in the light of the controversial concept of ideasthesia. The author proposes that the sonnet operates on three levels of sensory cognition: an initial stage of rational sensory segmentation, a subsequent synaesthetic fusion of odours, sounds and colours, and finally – an ideasthetic synthesis of feeling and knowing. The final stage of sensory processing triumphantly concludes the Symbolist quest for an elusive “beyond”, approximating the material and the ideal – the mechanism of which resembles an ideasthetic processing of sensory data. The poem mirrors the cognitive optimism characteristic of Baudelaire’s early thinking, soon to dissipate into melancholic (or Manichean) cognitive bankruptcy.